Consumprion and Islam: Micro Foundations and Macro Modelling - HASAN, Zubair (Journal of Economic and Social Thought, 2017)
Abstract. Function in Islamic economics. It starts with a brief look at the microelements of the concept and clears several cobwebs concerning wants and needs, scarcity of resources, the basket of goods, and the efficacy of utility and its maximization for consumer equilibrium. The explanations narrow down the conceptual gaps between the micro and macro level articulations of the subject. Next, the paper reviews some selected macro models resting on division of income on the basis of nisab between the upper (rich) and the lower (poor) classes of society for analyzing the impact of zakah-moderation mechanism on economic growth via the saving-investment route. It is demonstrated that, contrary to the claim based on models, the positive impact of Islamic scheme on the variables studied is uncertain, to put it mildly. Finally, attention is drawn to some recent developments in the treatment of consumption in economics as also to interest being shown in the subject in other social sciences. This inter-disciplinary approach seeks to detach consumption from income and links it to wealth. It also brings in environmental and ethical concerns into the picture. The effort promises to bring the treatment of consumption closer in the two economic disciplines, secular and Islamic: it is a welcome development. Keywords: Wants and needs, Micro foundations, Utility maximization; Macro models, Scarcity. JEL. D1, D11, E2.